Finite element analysis of a novel aircraft seat against static certification requirements (CS25.561) - Gulavani, Omkar Vitthal; Hughes, Kevin (Heriot-Watt University, 2011)
Due to the competitive nature of the airline industry and the desire to minimise aircraft weight, there is a continual drive to develop lightweight, reliable and more comfortable seating solutions, in particular, the development of a new generation slim economy seat. The key design challenge is to maximise the “living space” for the passenger, with strict adherence / compliance to Safety Regulations. This paper presents the analysis led design using finite element analysis of an innovative seat concept developed by BlueSKy Designers Limited, which has been acclaimed as “The most exciting development in aviation in over 30 years” and has won the company numerous awards. A generous angle of recline (40 degrees), movement of the “Seat Pan” along different gradients, and unique single “Forward Beam” design, distinguishes “Sleep Seat” from current generation seats. Compliance against Static Strength requirements (CS25.561) through a sequential model development approach was performed, in order to predict the stress induced in the primary seat structure, against static certification requirements. A critical design parameter is ensuring seat interface loads are below airline limits, which resulted in the inclusion of seat stud and track details in the finite element model. This stepwise and validated analysis framework, which includes mesh sensitivity studies, modelling of bolt-preload, representing bolted joints in FEA and obtaining a converged solution for non-linear FEA was essential in order to allow different concepts to be assessed virtually, thereby reducing development cycle time. The findings from this paper demonstrate that the seat is safe against CS 25.561.
Extended abstract
Keywords: Aircraft seat; CS 25.561; Non-linear FEA; Bolt Preload; Seat interface loads